THE ROLE OF ISLAMIC ECONOMICS IN OPTIMIZING THE FISHERIES AND MARINE POTENTIAL OF NATUNA REGENCY - Noni Vianti; Nurdian Setiawan; Kartubi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Natuna Regency possesses one of Indonesia's most extraordinary marine resource endowments, yet its fishing communities remain structurally underserved by Islamic economic institutions despite holding deep Islamic cultural values. This study examines the role of Islamic economics in Natuna's fisheries and marine sector and constructs a strategic optimization framework grounded in maqashid al-syariah principles. Employing a qualitative case study approach, data were collected through in-depth interviews with fishermen, local government officials, and Islamic economic practitioners, supplemented by observation and policy documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Findings reveal that Islamic economics operates at the level of informal cultural practice rather than formal institutional architecture, with profit-sharing arrangements and mutual assistance mechanisms present organically but unsupported by syariah-based financial institutions, productive zakat programs, or waqf-based infrastructure financing. The study constructs a four-pillar strategic framework encompassing maritime Islamic microfinance, productive waqf for fisheries infrastructure, sectoral zakat transformation, and ecological stewardship governance. This framework directly advances SDG 1, SDG 8, and SDG 14 by addressing financial exclusion, generating decent economic opportunities, and preserving the long-term ecological productivity of WPP 711. The study contributes the first systematic Islamic economics analysis specific to Natuna, offering a replicable model for Islamic maritime development in resource-rich coastal regions